NEXT-LEVEL SYSTEM DESIGN: ADVANCED AND HIGH-PERFORMANCE SYSTEM ARCHITECTURES FOR THE FUTURE OF ELECTRIC VEHICLES. - Sheeraz Ahmed; Muhammad Atif Imtiaz; Basit Ahmad; Jamil Ahmed; Aftab Ahmed Soomro; Muhammad Kashif Majeed; Fakhar Anjam; Mudassar Rafique (Spectrum of Engineering Sciences, 2025)
The transformation of the automotive industry toward electric mobility necessitates the development of advanced and high-performance system architectures to address the evolving demands of next-generation electric vehicles (EVs). With an increasing focus on sustainability, efficiency, and advanced technological integration, future EV platforms must support cutting-edge capabilities such as autonomous driving, smart energy management, and seamless connectivity. This paper investigates the design and integration of next-level system architectures that will define the future of electric vehicles. Emphasizing the need for modular, scalable, and fault-tolerant systems, the research explores how these architectures can facilitate continuous innovation, reduce vehicle obsolescence, and improve safety and reliability. Key topics include the integration of high-efficiency powertrains, advanced battery technologies, and intelligent control systems that enhance vehicle performance and user experience. Furthermore, the study highlights the role of emerging technologies such as artificial intelligence, machine learning, and vehicle-to-grid (V2G) communication in optimizing system performance, vehicle autonomy, and energy efficiency. The paper also examines the potential for adaptive architectures that can accommodate new functionalities and technological upgrades over the vehicle's lifecycle. By exploring these innovations, this research provides insights into how next-generation system designs will help electric vehicles meet the growing global demands for performance, safety, and environmental sustainability. The findings aim to guide the development of robust, future-proof EV architectures that will shape the automotive industry’s transition to a more sustainable and technologically advanced future.